Access to medicines: Experiences with compulsory licenses and government use - The case of Hepatitis C - Carlos María Correa; Germán Velásquez (South Centre, 2019)
This South Centre research paper discusses first, the limitations of the current research and development (R&D) model and its implications for access to medicines. Second, it considers the tension between intellectual property rights applied to medicines and States' observance of the fundamental right to health. Third, it examines the case of access to medicines for the treatment of Hepatitis C, illustrating the barriers to access created by intellectual property and the high prices normally associated with its exercise. Fourth, it presents the background, main aspects and obstacles to the achievement of the objectives of the Doha Declaration on the TRIPS Agreement and Public Health (2001). To conclude, this paper examines the experiences of compulsory licensing and government use of patents in Latin America (particularly in Ecuador, Peru and Colombia).
Keywords: 300; Arzneimittel; Immaterialgüterrechte; Gesundheitsversorgung; Menschenrechte; Infektionskrankheit; Welt